Native fluorescence spectroscopic characterization of DMBA induced carcinogenesis in mice skin for the early detection of tissue transformation. Issue 12 (21st June 2015) - Ebenezar, Jeyasingh; Aruna, Prakasa Rao; Ganesan, Singaravelu
<x xml:space="preserve">Abstract</x> The objective of the study is to characterize the endogenous porphyrin fluorescence in a dimethylbenz(a)anthracene (DMBA) induced mouse skin tumor model using native fluorescence emission and excitation spectroscopy.